First description of immature stages and redescription of female Bdella longicornis (Acari: Prostigmata: Bdellidae), with an ontogeny of chaetotaxy - Wu, You-Fang; Jin, Dao-Chao; Yi, Tian-Ci; Chen, Jian-Xin; Guo, Jian-Jun (Zootaxa, 2020)
Bdella longicornis (Linnaeus, 1758) is a widespread species. There has been no description of its immature stages before. In this paper, we redescribe its female adult and describe its four immature stages for the first time based on the specimens from P. R. China. Meanwhile, the ontogeny of chaetotaxy in B. longicornis is discussed.